Jawabanmu

Jawaban paling cerdas!
2014-04-20T21:21:39+07:00
a. f(x) = sin^2 x
         = (sin x)²
   f ' (x) = 2sinxcosx
           = sin2x
b. f(x) = cos^2 x
         = (cosx)²
   f '(x)= 2cosx(-sinx)
         = -2sinxcosx
         = - sin2x
c. f(x) = 6 sin x + 2 cos x
   f . (x) = 6cosx - 2sinx
d. f(x) = 2 cot x

         = 2cosx
             sinx
   f ' (x) =-2sinxsinx - 2cosxcosx
                     sin²x
           = -2(sin²x + cos²x)
                    sin²x
           = -2/sin²x
           = -2 cosec x